Epistemology, Fieldwork, and Anthropology - Sardan, Jean-Pierre Olivier de. author. aut Link
IX, 260 p.
Keywords: Epistemology, Fieldwork, and Anthropology provides a systematic examination of the empirical foundations of interpretations and grounded theories in anthropology. Olivier de Sardan explores the nature of the links between observed reality and the data produced during fieldwork, and between the data gathered and final interpretative statements. Olivier de Sardan's research asks how anthropologists develop a 'policy of fieldwork', what the advantages and limits of observation are, and if the dangers of over-interpretation and scientific ideologies be minimized. Exploring the space between epistemology and methodology, the book critically juxtaposes Anglo and Francophone writings about fieldwork, plausible interpretations, emicity, reflexivity, comparison, and scientific rigor.